2011
DOI: 10.1007/s10665-011-9506-0
|View full text |Cite
|
Sign up to set email alerts
|

A streamline approach to two-dimensional steady non-ideal detonation: the straight streamline approximation

Abstract: Detonations in non-ideal explosives tend to propagate significantly below the nominal one-dimensional detonation speed. In these cases, multi-dimensional effects within the reaction zone are important. A streamlinebased approach to steady-state non-ideal detonation theory is developed. It is shown in this study that, given the streamline shapes, the two-dimensional problem reduces to an ordinary differential equation eigenvalue problem along each streamline, the solution of which determines the local shock sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 15 publications
2
23
1
Order By: Relevance
“…It can be seen that the DNS results lie between those from the DSD approximation and SSA. This is consistent with results obtained by [14], who found that the SSA model gives too large a detonation velocity. At small radii the disparity between the DNS results and the SSA is significant and SSA gives a failure radius of (∼ 0.83 mm) compared to (∼ 1.25 mm) for the DNS calculations.…”
Section: Two-dimensional Calculationssupporting
confidence: 93%
See 3 more Smart Citations
“…It can be seen that the DNS results lie between those from the DSD approximation and SSA. This is consistent with results obtained by [14], who found that the SSA model gives too large a detonation velocity. At small radii the disparity between the DNS results and the SSA is significant and SSA gives a failure radius of (∼ 0.83 mm) compared to (∼ 1.25 mm) for the DNS calculations.…”
Section: Two-dimensional Calculationssupporting
confidence: 93%
“…Watt et al [14] have developed a more sophisticated model, the Straight Streamline Approximation (SSA) model. This makes no assumptions about the shock front curvature, instead it assumes that the post-shock streamlines are straight.…”
Section: Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the propagation of detonation waves in micro-channel charges is determined by nonlinear couplings between multidimensional effects and chemical kinetics, which makes the theoretical research very complex. Watt [17] et al studied the detonation velocities in detonation wave propagation by approximating the streamline in straight lines, but the result was found to be better when the charge was unconstrained. Xu [18] et al studied the detonation velocities of detonation waves in micro-channel explosives, but it was assumed that the curved detonation wave front is flat, which is not true.…”
Section: Introductionmentioning
confidence: 99%